Ketangguhan Mode I Sambungan Double Cantilever Beam Komposit Jute-Polypropylene Menggunakan Resistance Welding - Noviantoro, Mathias; Sukadana, I.G.K (Teknik Desain Mekanika, 2022)
Abstractt Currently around the world a lot of research is being done to develop composites made using plastic materials that are natural fibers. Jute / jute fiber is one of the natural fibers that are environmentally friendly, cheap and produced in large quantities. This study aims to determine the toughness of mode I of the jute-polypropylene composite double cantilever beam (DCB) connection using resistance welding. The composite was made with jute fiber as a reinforcing material and polypropylene (PP) as a binder. The composite was made with a ratio of 60% jute and 40% PP in 3 layers, the composite material was pressed until the composite thickness reached 3mm. The composite was cut to standard ASTM D-5528 size for toughness testing on DCB. Then the connection process is carried out using the electrical resistance welding method with two variations of niklin wire, namely niklin wire with a diameter of 0.3mm with 23 turns and 0.5mm with 21 turns. In this study, 3 specimens were used for each variation in diameter. The test was carried out using the mode I crack resistance test method with a head speed of 3mm/min and a load cell of 5 kN. The results showed that the composite which was joined using niklin wire had a stronger connection strength than the composite itself. Keywords: Composite, nikelin wire, welding resistance, DCB, mode I toughness